Diketopyrrolopyrrole-based functional supramolecular polymers: next-generation materials for optoelectronic applications. (June 2020) - Ghosh, Samrat; Shankar, Sreejith; Philips, Divya Susan; Ajayaghosh, Ayyappanpillai
Abstract: The very concept of dye and pigment chemistry that was long known to the industrial world underwent a radical revision after the discovery and commercialization of dyes such as mauveine, indigo, and so on. Apart from their conventional role as coloring agents, organic dyes, and pigments have been identified as indispensable sources for high-end technological applications including optical and electronic devices. Simultaneous with the advancement in the supramolecular chemistry of π-conjugated systems and the divergent evolution of organic semiconductor materials, several dyes, and pigments have emerged as potential candidates for contemporary optoelectronic devices. Of all the major pigments, diketopyrrolopyrrole (DPP) better known as the 'Ferrari Pigment' and its derivatives have emerged as a major class of organic functional dyes that find varied applications in fields such as industrial pigments, organic solar cells, organic field–effect transistors, and in bioimaging. Since its discovery in 1974 by Farnum and Mehta, DPP-derived dyes gained rapid attention because of its attractive color, synthetic feasibility, ease of functionalization, and tunable optical and electronic properties. The advancement in supramolecular polymerization of DPP-based small molecules and oligomers with directed morphological and electronic features have led to the development of high performing optoelectronic devices. In this review, we highlight the recent developments in the optoelectronic applications of DPP derivatives specifically engineered to form supramolecular polymers. Graphical abstract: Image 1 Highlights: Diketopyrrolopyrrole (DPP) is a highly potent dye for optoelectronic applications. DPP derivatives emerged as potential candidates in organic semiconductor devices. Easy-processability, low molecular weight, low cost of production, functional group accessibility. Tunable semiconductivity, broad optical absorption and exceptional (photochemical, mechanical and thermal) stability. A comprehensive review of the self-assembly of DPP derivatives pertinent to their optoelectronic properties is lacking. This review details recent reports on DPP–based systems, their synthesis, self–assembly and optoelectronic applications.